Growth and Production of Lemon Basil (Ocimum basilicum L.) Accessions Grown in Different Compositions of KCl Fertilizer and Cow Urine - Setiawan, Wawan; Tobing, Octavianus Lumban; Rahayu, Arifah (JURNAL AGRONIDA, 2019)
Lemon basil (Ocimum basilicum L.) is an indigenous plant which is commonly used as vegetable, medicinal herb, cosmetic ingredient, perfume ingredient, and food ingredient. This study was aimed at assessing the effects of the application of different compositions of KCl fertilizer and cattle urine on the growth and production of lemon basil accession. A factorial completely randomized design with two factors was used. The first factor was the composition of KCl fertilizer and cattle urine consisting of six levels, namely 100% R cattle urine 75% R cattle urine + 25% R KCl, 50% R cattle urine + 50% R KCl, 25% R cattle urine + 75% R KCl, 100% R KCl, and 0% R cattle urine + 0% R KCl. The second factor was lemon basil accession consisting of three levels, namely Bogor, Cianjur, and Sukabumi. Results showed that the composition of 25% R cattle urine + 75% R KCl and 100% R cattle urine gave leaf area and total yield dry weight, respectively, which were higher than those in other treatments. Bogor accession was found to have plant height, number of leaves, and length of branches which were significantly higher than those found in other accessions. Meanwhile, number of branches, leaf area, stem diameter, yield wet weight, and yield dry weight of Sukabumi accession were higher than those in Bogor and Cianjur accessions. Key words: Ocimum basilicum, leaf area, dry weight